The coexistence of neurofibromatosis type I and celiac disease in a child - Işık, İshak Abdurrahman and Akbulut, Ulaş Emre (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Işık İA, Akbulut UE. The coexistence of neurofibromatosis type I and celiac disease in a child. Turk J Gastroenterol 2018; 29: 522-3.